BETULIN AS A PROMISING SOURCE FOR OBTAINING ANTIVIRAL DRUGS - Pereslavtseva, A.V.; Galaiko, N.V. (Perm Federal Research Centre Journal, 2014)
The perspective of researching the development of effective antiviral drugs on the basis of semi- synthetic derivatives of natural origin pentacyclic triterpenoid betulin is discussed in the article. Significant attention is paid to estimating the possibility of using the triterpene derivatives to suppress the multiplication of enveloped viruses that cause socially dangerous infectious diseases – influenza, herpes, and HIV.